Fuzzy logic CD-ROM library - Cox, Earl.; McNeill, F. Martin 1937-; Dubois, Didier; Electrographics Electronic Imaging (Firm).; AP Professional (Firm). ([Chestnut Hill, Mass.] AP Professional, 1996)
Offers searchable versions of four books on fuzzy logic, sets, and systems.
The fuzzy systems handbook / Cox -- Fuzzy logic / McNeill, Thro -- Fuzzy sets and their application[s] to cognitive and decision processes / Zadeh -- Fuzzy sets and systems / Dubois, Prade.
Title from disc label.
Produced by Electrographics Electronic Imaging.
System requirements: Macintosh, Windows-compatible PC, DOS-compatible PC, or UNIX workstation; CD-ROM drive.
Keywords: Fuzzy logic -- Databases; Fuzzy sets -- Databases; Fuzzy systems -- Databases